2016
DOI: 10.1371/journal.pone.0164492
|View full text |Cite
|
Sign up to set email alerts
|

Practice Effects on Story Memory and List Learning Tests in the Neuropsychological Assessment of Older Adults

Abstract: Two of the most commonly used methods to assess memory functioning in studies of cognitive aging and dementia are story memory and list learning tests. We hypothesized that the most commonly used story memory test, Wechsler's Logical Memory, would generate more pronounced practice effects than a well validated but less common list learning test, the Neuropsychological Assessment Battery (NAB) List Learning test. Two hundred eighty-seven older adults, ages 51 to 100 at baseline, completed both tests as part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 60 publications
5
50
0
1
Order By: Relevance
“…Participants may have remembered the items/contexts or learned the contextual strategy in the 1 st test and therefore improved their memory and meta-memory performance in the 2 nd test. This result was consistent with the findings of practice effects of cognitive tests on learning and memory in the literatures for healthy and cognitively-impaired adults [51,52]. To minimize the potential practice effects of CMT, we recommended using the dual-baseline approach.…”
Section: Plos Onesupporting
confidence: 88%
See 1 more Smart Citation
“…Participants may have remembered the items/contexts or learned the contextual strategy in the 1 st test and therefore improved their memory and meta-memory performance in the 2 nd test. This result was consistent with the findings of practice effects of cognitive tests on learning and memory in the literatures for healthy and cognitively-impaired adults [51,52]. To minimize the potential practice effects of CMT, we recommended using the dual-baseline approach.…”
Section: Plos Onesupporting
confidence: 88%
“…We found generally better performance (i.e., higher scores and fewer prediction/estimation errors) in the 2 nd than the 1 st measurement in most CMT domains in both groups of participants. This finding indicates that there may be potentially practice effects of CMT in healthy and MCI participants [50,51]. Participants may have remembered the items/contexts or learned the contextual strategy in the 1 st test and therefore improved their memory and meta-memory performance in the 2 nd test.…”
Section: Plos Onementioning
confidence: 87%
“…Also, it is a known fact that neuropsychological test outcomes could be influenced by practice, or learning effects 40 , especially memory tests such as story and word list learning 41 (e.g., VVLT test). Therefore, specific attention should be on allocated to the number of training sessions and test execution.…”
Section: Discussionmentioning
confidence: 99%
“…Results of this study showed that increase in delayed memory may benefit from MoCA scale of 5 words in 3 repetitive memories generated by exercise. A longitudinal study showed that twice‐repeated practice effects affected memory of patients with MCI; through story‐memory and list‐learning tests, one study also showed significant effects of practice on delayed recall of MCI patients. Thus, based on practice effects and tolerance of elderly people to continuous intervention plan, group reminiscence program should be adjusted and improved in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Results of this study showed that increase in delayed memory may benefit from MoCA scale of 5 words in 3 repetitive memories generated by exercise. A longitudinal study 38 showed that twice-repeated practice effects affected memory of patients with MCI; through story-memory and list-learning tests, one study 39 Possibly, in long-term care facilities, admitted elderly people claim that they lack time perception. With increased degree of cognitive impairment, time-directed decline serves as sensitive indicator for cognitive function of patients.…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%